2021
DOI: 10.1111/coa.13740
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐clinical evaluation of a novel robotic system for transoral robotic surgery

Abstract: Current head and neck squamous cell carcinoma (HNSCC) treatment pathways involve combinations of surgery, radiotherapy and chemotherapy. Traditional radical surgery involves open procedures requiring jaw splits and wide visible incisions. These procedures carry high associated morbidity and postoperative quality of life outcomes are poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…During the previously published feasibility cadaver studies, significant tremor of the instrument and endoscope arms was experienced when the operating surgeon activated that arm 18. Four solutions to address this issue were undertaken.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the previously published feasibility cadaver studies, significant tremor of the instrument and endoscope arms was experienced when the operating surgeon activated that arm 18. Four solutions to address this issue were undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…The Versius Surgical System is usually deployed through laparoscopic ports into a visceral cavity. Initial trials suggested that when applied transorally, without laparoscopic ports, the instruments suffered from significant tremor 18. Optimisation of BSU and VPP placements combined with system developments has reduced the number of instrument arm clashes and addressed this limitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Versius is not currently CE marked or FDA approved for use within the head and neck and has not been clinically tested in this environment. Our study team has conducted pre-clinical dry lab and cadaveric evaluation of the system for transoral use completing a stage 0 assessment in accordance with the IDEAL framework of surgical innovation and concluded that clinical assessment of the system is appropriate however further development of instrumentation would be desired for wider clinical dissemination [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%